The anterolateral ligament (ALL) of the knee-Part of the iliotibial tract or a truly separate structure? - Brockmeyer, Matthias; Hoefer, Denis; Schaefer, Katja; Seil, Romain; Becker, Kurt; Paulsen, Friedrich; Kohn, Dieter; Tschernig, Thomas (Annals of Anatomy-Anatomischer Anzeiger, 2017)
In this Short Communication, the issue is discussed whether the recently reported anterolateral ligament of the knee is a unique structure or just part of the iliotibial tract. The presented findings from investigations in body donors support the view of a unique structure.
EVALuna2:35339